TRANSFORMATION METHODS OF SEWING PRESCHOOL CHILDREN’S CLOTHES (Journal of Science-Innovative Research in Uzbekistan, 2023)
The article will consider the technology of manufacturing transformable clothes for preschoolers. Children’s transformer clothing for preschoolers is in great demand today, as it is multifunctional, eco-friendly and convenient. One piece of clothing can be turned into another, which allows you to create a variety of clothing options in various stylistic solutions, create a unique image and remain stylish in any situation